The CUE domain of Cue1 aligns growing ubiquitin chains with Ubc7 for rapid elongation. - von Delbrück, M; Kniss, A; Rogov, V; Pluska, L; Bagola, K; Löhr, F; Güntert, P; Sommer, T; Dötsch, V (Elsevier, 2016)
Ubiquitin conjugation is an essential process modulating protein function in eukaryotic cells. Amazingly, little is known how the progressive assembly of ubiquitin chains is managed by the responsible enzymes. Only recently ubiquitin binding activity has emerged as an important factor in chain formation. The Ubc7 activator Cue1 carries a ubiquitin binding CUE domain, which substantially stimulates K48-linked polyubiquitination mediated by Ubc7. Our results from NMR-based analysis and in vitro ubiquitination reactions point out that two parameters accelerate ubiquitin chain assembly: the increasing number of CUE binding sites and the position of CUE binding within a growing chain. In particular interactions with a ubiquitin moiety adjacent to the acceptor ubiquitin facilitate chain elongation. These data indicate a mechanism for ubiquitin binding in which Cue1 positions Ubc7 and the distal acceptor ubiquitin for rapid polyubiquitination. Disrupting this mechanism results in dysfunction of the ERAD pathway by a delayed turnover of substrates